3D Conformal Fabrication of Piezoceramic Films. Issue 18 (28th April 2022) - Liu, Shiyuan; Shan, Yao; Hong, Ying; Jin, Yuankai; Lin, Weikang; Zhang, Zhuomin; Xu, Xiaote; Wang, Zuankai; Yang, Zhengbao
Abstract: Piezoceramic films are an essential class of energy‐conversion materials that have been widely used in the electronics industry. Although current methods create a great freedom for fabricating high‐quality piezoceramic films, it requires well‐controlled synthesis conditions, including special high‐cost equipment and planar substrates particularly. The limited substrate selections hinder the applications of piezoceramic films in 3D conformal structures where most objects possess complex curvilinear surfaces. To overcome such limitations, a fast, energy‐efficient, and cost‐effective approach, named flame treated spray (FTS) coating, is developed for preparing piezoceramic films on free‐form surfaces. The flame treatment significantly enhances the hydrophilicity of a substrate, assisting in forming a uniform and continuous thin film. The followed spray coating deposits hundreds of nanometers to several micrometers thick films on 3D free‐form surfaces. Given the size controllability and arbitrary surface compatibility of the FTS method, a highly conformal piezoelectric tactile sensor array (4 × 4) is assembled on a spherical surface for mimicking robot fingers and an on‐site thin‐film sensor on the wing of an aircraft model to monitor the vibration in real‐time during flight. The FTS film deposition offers a highly promising methodology for the application of functional thin‐film from micro‐ to marcoscale devices, regardless of conformal problems. Abstract : Functional ceramic films are available to be manufactured on freeform substrates for demanding applications via a facile flame treatment assisted spray coating process. The developed technique enables the conformal coating of piezoceramic thin films on various targets, including robotics, airplanes, etc.